Strategic Tax and Financial Reporting Decisions: Theory and Evidence* - MILLS, LILLIAN F.; SANSING, RICHARD C. (Contemporary Accounting Research, 2000)
Abstract This paper examines the effect of book‐tax differences on the probability that a transaction is audited and the probability that additional taxes are collected. It constructs a stylized model in which the taxpayer reports both financial accounting income and taxable income. The government observes both reports before deciding whether to conduct an audit. The analysis of the equilibrium yields two hypotheses. First, the probability that the government will audit a transaction is higher if the transaction generates a positive book‐tax difference (e.g., an expenditure that is deducted for tax purposes but capitalized for financial reporting purposes) than if the transaction generates no book‐tax difference. Second, conditional on being selected for audit, transactions with and without book‐tax differences are equally likely to have detected understatements of tax liability. These hypotheses are tested using Internal Revenue Service (IRS) data from the Coordinated Examination Program. The empirical tests are consistent with the predictions of the strategic tax compliance model.